26.5k views
4 votes
YOU BE THE TEACHER Your friend finds the sum.

9+(-6)=3
Is your friend correct?
yes
o no
Explain your reasoning.

User Justisb
by
5.2k points

2 Answers

5 votes

Answer:

The answer is 3, so she is correct!

Explanation:

Adding a negative is the same as subtracting a positive.

9+(-6)=3

9 - 6 = 3

3 =3

This is how the solution is 3!

Hope this helps! :)

User Shitesh
by
5.9k points
5 votes

Answer: My friend is correct.

Step-by-step explanation:

Adding a negative is the same as subtracting a positive.


9 + (-6) = 3


9 - 6 = 3


3 = 3

Hope this helps! Have a great day!

User Everyman
by
5.4k points